Crafting trade and investment accords for sustainable development Athena's treaties - Cordonier Segger, Marie-Claire 1973- (Oxford Oxford University Press, 2021)
International economic law guides and shapes globalization and the future of the world economy, our human societies, and the Earth. The rules which facilitate trade and investment could defend the interests of Hermes, Greek god of commerce and thieves, or learn to draw inspiration from Athena, goddess of justice, wisdom, and crafts. This volume explores how trade and investment agreements could promote more sustainable development, rather than increasing the negative social and environmental impacts of economic growth. States and other actors are attempting to integrate social and environmental considerations into trade and investment policies, towards more sustainable development. Analysing their efforts, this volume offers insights into the ways that commitments to sustainability are being operationalized in the texts of economic treaties themselves. Written by a renowned expert jurist and professor of law, this book examines the measures being debated in the WTO and adopted by States in a selection of innovative and flexible regional and bilateral trade and investment accords. With legal examples spanning decades of experimentation and experience, the book illuminates how States and stakeholders are seeking innovative ways to integrate environmental and social considerations into trade and investment agreements. Introducing a ground-breaking systematic approach, the volume considers how, through this integration, international trade and investment law can contribute to the achievement of the world's Sustainable Development Goals.
ELECTION ONE: INTRODUCTION -- 1. Introduction -- 2. International trade, investment and sustainability -- 3. Advancing trade and investment rules for the world's sustainable development goals (SDGs) -- SECTION TWO: ENVIRONMENTAL AND SOCIAL IMPACTS OF TRADE AND INVESTMENT AGREEMENTS -- 4. Trade and investment treaties and their impacts -- 5. Material impacts of trade and investment on sustainable development -- 6. Normative intersections of trade, investment and sustainability measures -- SECTION THREE: INTEGRATION OF ENVIRONMENTAL AND SOCIAL CONSIDERATIONS INTO TRADE AND INVESTMENT AGREEMENTS -- 7. International legal reasons for countries to address environmental and social impacts of trade and investment agreements -- 8. Integration as a principle of European law, and its relevance to the negotiation of trade and investment agreements -- 9. Policy and 'soft law' rationales for addressing social and environmental concerns in trade and investment treaties -- 10. International trade and investment agreements in light of the integration principle -- SECTION FOUR: WTO PROVISIONS AND PROCESSES ON SUSTAINABLE DEVELOPMENT -- 11. Development and environment in early world trade debates -- 12. Sustainable development provisions in the 1994 GATT/WTO agreements -- 13. Sustainable development in the 2001 WTO Doha round debates -- 14. Sustainable development in the WTO institutions and trade policy review mechanism (TPRM) -- 15. The limits of addressing sustainable development in the WTO regime -- SECTION FIVE: SUSTAINABLE DEVELOPMENT-RELATED INNOVATIONS IN BILATERAL AND REGIONAL TRADE AND INVESTMENT RULES -- 16. Bilateral and regional economic rules and regimes -- 17. Provisions to integrate environmental and social considerations in to a bilateral and regional trade and investment agreements for sustainable development -- 18. Procedural innovations related to sustainable development -- SECTION SIX: TRADE AND INVESTMENT LAW CONTRIBUTIONS TO THE SUSTAINABLE DEVELOPMENT GOALS -- 19. Trade and investment accords for sustainable development goals 1-5 -- 20. Trade and investment accords for sustainable development goals 6-11 -- 21. Trade and investment accords for sustainable development goals 12-17 -- SECTION SEVEN: A FUTURE TRADE AND INVESTMENT LAW FOR SUSTAINABLE DEVELOPMENT -- 22. Integrating social and environmental considerations into trade and investment agreements, for sustainable development -- 23. A future agenda for crafting 'Athena's treaties' on trade and investment for sustainable development
Includes bibliographical references (pages 401-426) and index.
Keywords: Environmental law, International. -- Electronic book; Foreign trade regulation; Investments -- Law and legislation; Sustainable development -- Law and legislation; Environmental law, International; Foreign trade regulation; Investments -- Law and legislation; Sustainable development -- Law and legislation